Teach us to pray: the Lord's prayer, catechesis, and ritual reform in the sixteenth century - Mahon, Katharine (Lexington Books/Fortress Academic, 2019)
The Lord's prayer: a lens into a ritual system -- The ritual functions of the Lord's prayer in medieval patterns of Christian formation -- Reritualizing catechesis: the Lord's prayer in Reformation catechisms -- Reritualizing liturgical participation: the Lord's prayer in Reformation liturgy -- Teaching how to pray: reritualizing lay private prayer -- Conclusion: reforming ritual and reritualizing Christian formation.